ISLAMIC LEGAL REVIEW OF CLOTHING SALES USING THE BAL SYSTEM AT TANRUTEDONG MARKET, SIDENRENG RAPPANG REGENCY - Pananrang, Asbar; Muhammad Yaasiin Raya; Muh. Taufiq Amin (El-Iqthisadi, 2024)
Abstract The practice of selling clothing at Tanrutedong Market in Sidrap Regency presents challenges for sellers and retailers because they cannot directly see the condition of the clothes purchased from agents. The clothes are typically sold in bales, so sellers can only evaluate the condition of the items after they arrive. This study focuses on two research questions: 1) What is the form of the sale and purchase transaction of clothing using the bal system? 2) What is the Islamic legal perspective on this transaction? This qualitative research employs a normative and sharia approach. The data sources include sellers/retailers and buyers at Tanrutedong Market, with data collection methods involving observation, interviews, and documentation. Data analysis is conducted in three stages: data reduction, data presentation, and conclusion drawing. The findings reveal that imported clothing is ordered in bales from distributors and sold individually. Sellers cannot ascertain the condition and quality of the goods, which potentially leads to ambiguity (gharar). Although there are elements of uncertainty, the sale of second-hand imported clothing at Tanrutedong Market mostly meets the criteria in Islamic commercial law and is not considered directly detrimental to buyers. Keywords: Islamic Law, Sale and Purchase, Bal System, Tanrutedong Market.